Chronic rhinosinusitis unveiling a two decades ethmoid foreign body: a case report - Fitria Waffi Nur Aini; Feri Trihandoko (Universitas Muhammadiyah Surabaya, 2025)
We report a case of a 50-year-old female who presented with rhinosinusitis-like symptoms, which she had been experiencing intermittently for over two decades. Her medical history revealed a nasal surgery performed approximately 22 years ago, after which she continued to experience unresolved symptoms despite multiple treatments. A Computed Tomography (CT) scan of the paranasal sinuses revealed findings with ethmoiditis, prompting the decision for endoscopic sinus surgery to address the underlying pathology. During surgery, a 3 cm gauze was discovered after opening the posterior ethmoid sinus. We highlight an unexpected foreign body inside the ethmoid sinus based on an unidentified picture from the CT scan, which we accidentally discovered during endoscopic surgery. This case underscores the importance of considering a retained foreign body as a potential cause of chronic rhinosinusitis, even many years after the initial surgical intervention. The unexpected identification of the gauze, which was not depicted in the preoperative CT scan, highlights the challenges in diagnosing retained foreign bodies within the complex anatomy of the sinuses. The report discusses the clinical presentation, diagnostic challenges, and management of this unusual case, contributing valuable insights to the literature on chronic rhinosinusitis and retained foreign bodies in the sinonasal region.